(100)-Oriented gallium oxide substrate for metal organic vapor phase epitaxy for ultraviolet emission. Issue 18 (15th April 2020) - Li, Weijiang; Guo, Liang; Zhang, Shengnan; Hu, Qiang; Cheng, Hongjuan; Wang, Junxi; Li, Jinmin; Wei, Tongbo
Abstract : High-quality low-stress GaN and MQWs emitting in the UV region were grown on (100) β-Ga2 O3 by MOVPE using a pulsed-flow method. Abstract : In this work, we demonstrated the growth of high-quality GaN epilayers and InGaN/GaN multiple quantum wells (MQWs) with 400 nm emission on a (100) β-Ga2 O3 substrate. The dislocation density of GaN epilayers may be obviously reduced by pulsed-growth, attributed to the enhanced three-dimensional to two-dimensional transformation process. A three-stage growth model had been proposed to clarify the underlying mechanism. Furthermore, pulsed-flow growth also enabled the relatively low-stress state (0.12 GPa) of GaN on (100) β-Ga2 O3 . Due to the decreased quantum confined Stark effect (QCSE), the MQWs on pulsed-GaN exhibited a lower blue-shift with increased excitation power densities and showed an increased recombination rate. Additionally, a tendency for GaN separation was also observed, beneficial to heat dissipation of devices on (100) β-Ga2 O3 . This work may provide a prospective way to fabricate high-performance vertical structure ultraviolet light emitting diodes (LEDs) on (100) β-Ga2 O3 substrates.